Conversion of Oil Palm Empty Fruit Bunches Using The Pyrolysis Into Bio-Oil and Its Characterization for Biopesticide - Sari, Frisa Rahmah; Mayub, Afrizal; Nursa'adah, Euis (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2023)
Oil palm empty fruit bunches (EFB) is a by-product of processing CPO (Crude Palm Oil) at a palm oil processing factory. The accumulation of Oil Palm EFB waste could cause environmental problems in the future. One of the optimal ways to reuse oil palm EFB waste is to convert it into bio-oil using pyrolysis. Bio-oil contains phenol, acid compounds, and their derivatives with antioxidant and antimicrobial, which makes them suitable for biopesticides. This study aims to produce Bio-Oil by pyrolysis at different temperatures and analyze its characterization for use as a biopesticide. Oil Palm EFB characterization was carried out by measuring the yield and pH and analyzing the Phenol and Acetic Acid compounds in the pyrolysis products at 100oC, 150oC, and 245oC. Yield analysis was carried out by comparing the mass of the Bio-Oil produced with the mass of the Oil Palm EFB raw material used. Phenol was determined using the Folin-Ciocalteu reagent, and absorbance was measured using UV-Vis spectrophotometry, acetic acid was determined using the titrated acid-base method, and pH was measured using a pH meter. The results showed that the parameter of temperature in pyrolysis affected the concentration of the chemical compounds produced. The results showed that the pyrolysis temperature parameter affected the concentration of the chemical compounds produced. Treatment at 150oC- 245oC is the best result due to the parameters that have been analyzed. The characteristics of the Bio-oil produced are a yield of 29.63%-100%, total phenol of 1.04%-3.87%, total acid of 1.12%-2.14%, and a pH value of 4.09 - 4.16. The characteristics of this Bio Oil can be used as a biopesticide that complies with the Indonesian National Standard (SNI).